The Role of Marketing Management Through Social Media Instagram on Scarf By Miwa in Aceh Singkil - Araza Yudha Magfira; Nurbaiti Nurbaiti; Sella Fauziati Harlina (Penerbit Jurnal Indonesia, 2022)
Bymiwa scarf is one of the businesses in the field of hijab that is in great demand by the public. scarfbymiwa sells various kinds of headscarves with various motifs, the hallmark of scarfbymiwa is selling various kinds of veils (hijab) with various motifs and made of voal cotton. Knowing the implementation of marketing management in the scarfbymiwa business through Instagram social media (3) Evaluating the scarfbymiwa marketing management through Instagram social media (4) Following up the scarfbymiwa business. The method used is descriptive with a qualitative approach. The subject of this research is Ownerscarfbymiwa, and 30 scarfbymiwa consumers from various circles, the determination of research subjects is done by interviewing respondents. Data was collected using observation techniques, interview techniques and documentation techniques. The results showed that the role of marketing management was very helpful in marketing scarfbymiwa products on Instagram. From the owner who is very good at marketing through Instagram social media, then consumers really appreciate Instagram social media marketing and 30 consumers 9 (90%) like Instagram social media marketing and often use it while 1 respondent (10%) likes but doesn't like it in social media marketing. product photo design is lacking because it is attractive. Therefore, it is necessary to pay more attention to uploading products, to pay more attention to product photo designs.